Ulasan Kritis Teori Permintaan Kesehatan Grossman - Devi Indah Erlita; Yukha Sundaya (Bandung Conference Series: Economics Studies, 2022)
Abstract. Grossman (1972) pioneered health economic analysis. The series of studies that have been arranged partly presents a critique of Grossman's (1972) theory and partly applies it to formulate health management policies. This study aims to present a critical review analysis of the literature focusing on health demand. The conclusions of this study regarding health demand are pioneered by the theory described by Grossman (1972) regarding health problems which are analyzed from the point of view of economic demand. Some factors can affect the demand for health, namely economic and non-economic factors. Economic factors consist of food commodity prices, health commodity prices, and per capita income described in the research of Erokhin & Gao (2020), Saliem et al., (2020), Uche et al., (2021), Budiarto (1996), Galama & Kippersluis (2018), Hartwig & Sturm (2017), Frank & Mcineka (2021), Damayanti et al., (2017). Non-economic factors such as education, immunization, and food consumption are described in the studies of Cutler & Muney (2012), Galama (2015), Damayanti et al., (2017), Hartwig & Sturm (2017), Galama & Kipperluis (2018). Abstrak. Grossman (1972) mempelopori analisis ekonomi kesehatan. Serial studies yang tersusun, sebagian menampilkan kritisisme terhadap teori Grossman (1972), dan sebagian lagi mengaplikasikannya untuk merumuskan kebijakan pengelolaan kesehatan. Tujuan dari penelitian ini adalah menampilkan analisis ulasan kritis terhadap literatur yang berfokus pada permintaan kesehatan. Kesimpulan dari penelitian ini mengenai permintaan kesehatan di rintis oleh teori yang dijelaskan oleh Grossman (1972) mengenai masalah kesehatan yang dianalisis dari sudut pandang permintaan ekonomi. Terdapat faktor yang dapat mempengaruhi permintaan kesehatan yaitu faktor ekonomi dan faktor non ekonomi. Faktor ekonomi terdiri dari harga komoditas makanan, harga komoditas kesehatan, pendapatan perkapita yang dijelaskan dalam penelitian Erokhin & Gao (2020), Saliem et al., (2020), Uche et al., (2021), Budiarto (1996), Galama & Kippersluis (2018), Hartwig & Sturm (2017), Frank & Mcineka (2021), Damayanti et al., (2017). Faktor non ekonomi seperti pendidikan, imunisasi, dan konsumsi makanan dijelaskan dalam penelitian Cutler & Muney (2012), Galama (2015), Damayanti et al., (2017), Hartwig & Sturm (2017), Galama & Kipperluis (2018).